STAFFING DALAM ALQURAN DAN HADIS DITINJAU DARI MANAJEMEN PENDIDIKAN - Tuti Andriani (Sosial Budaya, 2015)
Staffing in an organization can be defined as a series of processes and efforts to acquire, develop, motivate, and evaluate the overall human resources. It is required within the organization in achieving its goals. In staffing, putting a person in a work should be in accordance with his capabilities and expertise so that all are expected to be achieved. Job placement principle is the principle of humanity, democracy, the right man on the right place, equal pay for equal work, unity of direction, the principle of unity of purpose, unity of command, Efficiency and Productivity Work. The concept is the placement, promotion, transfer and demotion. Staffing in the Qur'an and Hadith seen from education management is an employee must complete properly, responsibility, trust, has the capability and expertise, serve, work ethic, strong and trustworthy, honest, sincere, true and trustful, physical and mental strength, and high manners. Professionalism in view of sharia is characterized by three things, namely ahliyah (expertise), himmatul 'charity (high work ethic), trustworthy (reliable).